2022
DOI: 10.1016/j.cegh.2022.100967
|View full text |Cite
|
Sign up to set email alerts
|

The impact of casirivimab-imdevimab antibody cocktail in patients amidst and post COVID 19 treatment: A retro-prospective comparative study in India

Abstract: Background Monoclonal antibodies have gained attention in developing countries owing to its benefits portrayed by few clinical trials. However, no studies until now have been undergone in India. Methods A retro-prospective comparative observational study was conducted in symptomatic COVID19 patients to evaluate the impact of Casirivimab and Imdevimab antibody cocktail in the high-risk population. Through an extensive data retrieval for 6 months, 152 samples were documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…Anti-SARS-CoV-2 mABs therapies are generally well-tolerated in patients suffering from COVID-19. 47,[54][55][56][57] Our study has some important limitations. First, a significant publication bias was detected in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Anti-SARS-CoV-2 mABs therapies are generally well-tolerated in patients suffering from COVID-19. 47,[54][55][56][57] Our study has some important limitations. First, a significant publication bias was detected in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 94%
“…showed that neutralising mABs are safe and not associated with a higher risk of adverse events compared to placebo. Anti‐SARS‐CoV‐2 mABs therapies are generally well‐tolerated in patients suffering from COVID‐19 47,54–57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients were instructed not to take any vaccine till 90 d after taking the antibody treatment regimen [24,25] . This study also reported a reduction in the need for mechanical ventilation and Intensive Care Unit (ICU) support following CAS and IMD, even for the non-immunized patients which could be owing to efficacy of the antibody cocktail's reduced response to interfering with the vaccine-induced immune response [26] . A similar study was also in agreement with the current findings [27] .…”
Section: Resultsmentioning
confidence: 71%
“…Aneesh et al in a retro-prospective study showed that need for mechanical ventilation and high flow oxygen requirement were significantly low in casirivimabimdevimab treated patients when compared to patients with standard treatment. 14 There was a case of anaphylaxis in one of the patients who received the drug and it was promptly treated. We recommend giving casirivimab-imdevimab at hospital setup where adequate facilities for resuscitation are available.…”
Section: Discussionmentioning
confidence: 99%